2007
DOI: 10.1155/2007/862917
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-Release Oral Mesalamine 4.8 g/day (800 mg tablets) Compared with 2.4 g/day (400 mg tablets) for the Treatment of Mildly to Moderately Active Ulcerative Colitis: The ASCEND I Trial

Abstract: Delayed-release oral mesalamine is an effective and well-tolerated initial therapy in patients with mildly to moderately active UC, and a 4.8 g/day dose may enhance treatment success rates in patients with moderate disease compared with mesalamine 2.4 g/day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
105
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(112 citation statements)
references
References 10 publications
3
105
0
4
Order By: Relevance
“…Two dose-ranging studies of Eudragit-S-coated pH-dependent release mesalamine show a dose -response relationship, comparing 2.4 g daily with 4.8 g daily, with a greater clinical response to the higher dose seen in patients with moderate but not mild disease. No diff erences were seen, however, in complete remission rates between the two dosages ( 134,135 ). Similarly, there were no signifi cant diff erences in clinical responses or remissions in patients with mild or moderate disease when treated with multimatrix-mesalamine with 2.4 g daily compared to 4.8 g daily ( 83,132 ).…”
Section: Recommendations For Maintenance Of Remission In Distal Diseasementioning
confidence: 83%
“…Two dose-ranging studies of Eudragit-S-coated pH-dependent release mesalamine show a dose -response relationship, comparing 2.4 g daily with 4.8 g daily, with a greater clinical response to the higher dose seen in patients with moderate but not mild disease. No diff erences were seen, however, in complete remission rates between the two dosages ( 134,135 ). Similarly, there were no signifi cant diff erences in clinical responses or remissions in patients with mild or moderate disease when treated with multimatrix-mesalamine with 2.4 g daily compared to 4.8 g daily ( 83,132 ).…”
Section: Recommendations For Maintenance Of Remission In Distal Diseasementioning
confidence: 83%
“…This would explain why the mean dose of MSZ was significantly higher in patients who had had at least one flare-up in the previous year compared to patients who were in remission at the time of data collection. Results obtained in ASCEND I/II trials indicated that 4.8 g/day MSZ provides statistically significant higher rates of mucosal healing and sigmoidoscopic improvement within a 6-week period when compared with a 2.4 g/day dosing regimen in patients with moderately active UC (20)(21)(22). Takeshima et al conducted a multicenter retrospective study to investigate the efficacy of continuous maintenance treatment with 4.0 g/day of MSZ (23).…”
Section: Discussionmentioning
confidence: 99%
“…The ASCEND trials were a series of dose-finding trials for 5-ASA in UC. The ASCEND I trial studied patients with mild-moderate UC treated for 6 weeks with either 4.8 or 2.4 g/day of an oral delayed release Eudragit S formulation of 5-ASA (Asacol Õ ) administered as divided doses TID [Hanauer et al 2007]. There was no significant difference between the 4.8 and 2.4 g/day doses of 5-ASA in achieving overall clinical improvement (i.e.…”
Section: Maintenance Of Remission In Ulcerative Colitismentioning
confidence: 99%